Multilevel Influences on Voluntary Workplace Green Behavior: Individual Differences, Leader Behavior, and Coworker Advocacy - Kim, Andrea; Kim, Youngsang; Han, Kyongji; Jackson, Susan E.; Ployhart, Robert E. (Journal of Management, 2017)
Drawing on a multilevel model of motivation in work groups and a functionalist perspective of citizenship and socially responsible behaviors, we developed and tested a multilevel model of voluntary workplace green behavior that explicates some of the reasons why employees voluntarily engage in green behavior at work. For a sample of 325 office workers organized into 80 work groups in three firms, we found that conscientiousness and moral reflectiveness were associated with the voluntary workplace green behavior of group leaders and individual group members. Furthermore, we found a direct relationship between leader green behavior and the green behavior of individual subordinates as well as an indirect relationship mediated by green advocacy within work groups. Our theory and findings shed new light on the psychological and social conditions and processes that shape voluntary workplace green behavior in organizational settings and suggest implications for organizations striving to improve their social responsibility and environmental sustainability.